Politeness Strategy in The First Debate of the 2024 Indonesian Presidential Candidate - Saragih, Febrianta Lidia; Lestari, Febrika Dwi; Sinaga, Nenni Triana (Lembaga Riset Mutiara Akbar, 2025)
This study aims to determine the types and strategies of politeness that are dominant in the first debate of the 2024 Indonesian presidential candidates. Qualitative descriptive methods are used in this study to collect data to explore politeness strategies in the first debate of the 2024 Indonesian presidential candidates. Data collection was carried out by observation, as additional data to find out more about the success of politeness strategies in the debate. Data were taken from video scripts from the first debate of the 2024 Indonesian presidential candidates. Data analysis was used by Brown and Levinson (1992) who classified five politeness strategies of lecturers' speech. Based on the analysis, it was found that four types of politeness strategies occurred in the first debate of the 2024 Indonesian presidential candidates, there were 47 utterances data including 8 off-record utterances, 27 positive politeness utterances, 3 negative politeness utterances and 9 bald on record utterances. The most dominant strategy used by the 2024 Indonesian presidential candidates is positive politeness. It is hoped that this study can increase understanding about the types and functions of politeness strategies in conversation and adds deeper insight.